PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS, PELATIHAN, DAN MOTIVASI GURU TERHADAP PENINGKATAN KINERJA GURU SEKOLAH DASAR NEGERI GUGUS 20 KECAMATAN CIPUTAT TIMUR - Mimchatul Maula; Siti Zubaidah; Saiful Anwar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The quality of education in Indonesia remains a government priority as outlined in relevant laws and regulations, with teacher performance serving as the main pillar in educating, teaching, guiding, and evaluating students according to competency standards. Initial observations at SD Negeri Gugus 20, East Ciputat District, South Tangerang City, revealed low teacher performance (52.5% issues in work quality such as unstructured lesson plans and weak mastery of material; 65.86% poor work quantity; 56.36% low effectiveness; 65.23% weak collaboration), triggered by suboptimal democratic leadership style, minimal post-pandemic training, and low motivation. Such conditions can be addressed for curriculum innovation. This associative quantitative research examines the influence of democratic leadership style, training, and motivation on teacher performance through a 40-item questionnaire (Likert 1-5, reverse scoring), analyzed using SPSS 27 (normality, linearity, multicollinearity, heteroscedasticity, regression tests). The results show a significant positive influence from all three variables, with policy implications including routine training, effective democratic leadership, and motivation programs to improve teacher performance in public elementary schools.Keywords: teacher performance, democratic leadership, teacher training, motivation, elementary education